2011
DOI: 10.1128/aac.05429-11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Isoniazid, Rifampin, and Pyrazinamide in Children Younger than Two Years of Age with Tuberculosis: Evidence for Implementation of Revised World Health Organization Recommendations

Abstract: There was no difference in the t max values achieved. Children less than 2 years of age achieve target concentrations of first-line anti-TB agents using revised WHO dosage recommendations. Our data provided supportive evidence for the implementation of the revised WHO guidelines for first-line anti-TB therapy in young children.Isoniazid (INH), rifampin (RMP), and pyrazinamide (PZA) are routinely used to treat tuberculosis (TB) in children (23, 44). Recommendations for pediatric dosages are based on a small num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
95
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 34 publications
13
95
2
1
Order By: Relevance
“…A proposed PZA adult target range of 20 to 60 g/ml has been suggested (23), but a study from Botswana showed that a C max of less than 35 g/ml was associated with a poor outcome in adult pulmonary TB patients (39). Our results were similar to other pediatric studies reporting peak concentrations of 34.6 to 47.8 g/ml when dosed at 30 to 40 mg/kg (8,13,28,32).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A proposed PZA adult target range of 20 to 60 g/ml has been suggested (23), but a study from Botswana showed that a C max of less than 35 g/ml was associated with a poor outcome in adult pulmonary TB patients (39). Our results were similar to other pediatric studies reporting peak concentrations of 34.6 to 47.8 g/ml when dosed at 30 to 40 mg/kg (8,13,28,32).…”
Section: Discussionsupporting
confidence: 81%
“…RMP mean peak concentrations of 6.4 and 11.7 g/ml, when dosed at 10 and 15 mg/kg (P ϭ 0.005), respectively, were observed in 11 South African children younger than 2 years of age using a different RMP formulation. The authors noted that children with high drug concentrations at the lower RMP dose did not necessarily have comparatively high drug concentrations following the higher dose (13). RMP formulations are known for considerable intra-and interindividual variability, which may partly be explained by differences in RMP bioavailability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetic sampling was done at five time points (time zero and 1, 2, 4, and 8 hours postdose) but not over the entire 24-hour dosing interval, and so we could not determine the trough concentrations of the drugs. However, such a sampling scheme has been used in other pediatric studies, when sampling at steady state is considered sufficient to estimate key pharmacokinetic parameters such as C max and AUC up to the time of the last sample (33,34). The factors selected in the multivariate analysis do not explain all the interindividual variability in the pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected at time zero (predose) and at 1, 2, 4, and 8 hours postdose. This sampling scheme, when conducted at steady state, was considered sufficient to estimate key pharmacokinetic parameters such as maximum concentration (C max ) and area under the concentration-time curve (AUC) (33). The samples, collected in EDTA-coated tubes, were placed immediately on ice and centrifuged within 30 min at 3,000 ϫ g for 10 min.…”
Section: Methodsmentioning
confidence: 99%